EVALUATION OF MUSA ACUMINATA FRUIT AS A NATURAL SUPERDISINTEGRANT FOR TABLET FORMULATION - E, Gopinath (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present work was to develop and evaluate a new, low-cost effective superdisintegrant from Musa acuminata fruit for tablet formulation. Methods: The study involved collection of M. acuminata fruit powdered and evaluated for physicochemical properties. Propranolol Hcl was used as a model drug for tablet formulation. Different concentrations of M. acuminatea powder were used as superdisintegrant, and orodispersible tablet is prepared and evaluated. In the present study, sodium starch glycolate was used as synthetic superdisintegrant for comparative study. Result: The powder was dark brownish and did not change throughout the study. The percentage porosity of powder was found to be 42.88% and angle of repose of was found to be 33.69°. The solubility study shows that the powders are sparingly soluble in water and disperse into individual particles. Total ash and acid insoluble ash values of powder were found to be 2.61 and 2.11% w/w, respectively. The average weight of tablets was ranged from 101.42 to 103.52 mg and averaged hardness was found to be 3.4 kg/cm2. Moreover, the tablets exhibited acceptable friability. Disintegration time of all formulations was found to be in the range of 22–80 s and wetting time was found to be 07–18 s. Conclusion: From the study, it was concluded that M. acuminatea powder in the range of 2–12% can be used as superdisintegrant in orodispersible tablet formulation and shall be preferred as having nutritive value as well as cost profit in the development of orodispersible tablet than synthetic polymer.